Synthesis, Characterization and Performance of Materials for a Sustainable Future - John Vakros; Evroula Hapeshi; Catia Cannilla; Giuseppe Bonura (Nanomaterials, 2023)
Today, sustainability represents the key factor for economic progress in compliance with social advancement and environmental protection, driving innovation in materials, processes and technologies [...]